Issues in relation to contract formation and form requirements in internet contracting - R.A. Kadir (University of Sheffield, 2012)
The thesis compares and contrasts the formation and form requirement rules of England and Malaysia, and the ultimate objective is to suggest reform for the Malaysian law which does not work well with the facilitation of electronic commerce.